Petrography and geochemical characterisation of the Permo-Triassic in the Sierra de Varela, San Luis, Argentina - Tobares, María Laura (2015)
The Choiyoi Group reflects the initial breakdown of Gondwana in the Permo-Triassic. Thegroup outcrops over large areas of the Andes and the centre of Argentina. In this regard, the pyroclastitesof the Sierra de Varela, in the province of San Luis, were recognised as an integral part of the ChoiyoiGroup. Knowledge about the physical and chemical characteristics of this unit in San Luis is scarce. Thepaper presents results about the stratigraphy, petrography and geochemistry of the Cerro Varela formation,in the hill of the same name, and investigates the possible depositional environment for the sequence.The bulk of the rocks correspond to welded and non-welded tuffs of rhyolitic composition. Thewelded tuffs would represent the transition towards an intraplate complex of alkaline character. In contrast,non-welded tuffs exhibit a predominant calc-alkaline signature of variable K2O contents, possiblyrelated to their formation in a volcanic-arc environment. Distinctive rock populations are alsoevidenced by the content of traces and rare earth elements. Deposition would have resulted from pyroclasticflows in a Plinian explosion. It is argued that the welded tuffs correspond to basal ignimbrites,whilst the unconsolidated fraction is indicative of fallout deposits moved to the distal parts of the flow.